Genetic Variation in the ZNF208 Gene at rs8103163 and rs7248488 Is Associated With Laryngeal Cancer in the Northwestern Chinese Han Male - Wang, Shiyang; Wen, Xiulin; Zhao, Ruimin; Bai, Yanxia (Frontiers in Genetics, 2022)
Background: Laryngeal cancer is more common in middle-aged and older men. We conducted an association analysis between ZNF208 polymorphisms and laryngeal cancer (LC) risk in Northwestern Chinese Han male. Methods: A total of 352 subjects (LC patients and 180 controls) were involved in this study. Agena MassARRAY was used to determine the genotypes. Unconditional logistic regression analysis was performed to explore the relevance. Results: Two SNPs were associated with the risk of LC: rs8103163, OR = 1.41, p = 0.043; rs7248488, OR = 1.45, p = 0.025. Furthermore, rs8103163 was associated with an increased risk of LC under log-additive model (OR = 1.40, p = 0.042), and rs7248488 was related to a higher risk of LC under recessive model (OR = 2.33, p = 0.025) and log-additive model (OR = 1.44, p = 0.026). Conclusions: We first demonstrated that the rs8103163 A allele, rs7248488 A allele in ZNF208 create susceptibility to Laryngeal cancer in Northwestern Chinese Han male.